Motivasi Tokoh Utama Novel Merry Riana: Mimpi Sejuta Dolar Karya Albertheine Endah (Tinjauan Psikologi Abraham Maslow) (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This study aims to describe the motivational aspects of the main character in the novel Merry Riana Mimpi Sejuta Dolar by Alberthiene Endah, a psychological review of Abraham Maslow. This type of research is qualitative descriptive research. This qualitative research makes the researcher the key instrument. The data collection techniques used are documentation techniques, reading techniques, and note-taking techniques. Data analysis techniques use data reduction, data presentation, inference and verification. Finally, data validity checking is done by triangulation. The results showed two things, first, the existence of motivation in the novel Merry Riana: A Million Dollar Dream by Albetheine Endah which includes: motivation to meet physiological needs, motivation to meet security needs, motivation to meet social needs, motivation to meet self-esteem needs, and motivation to meet self-actualisation needs. In addition, another motivation was also found, namely economic motivation.